Usefulness of Serum as a Non-Invasive Sample for the Detection of Histoplasma capsulatum Infections: Retrospective Comparative Analysis of Different Diagnostic Techniques and Quantification of Host Biomarkers - L. Bernal-Martínez; P. De la Cruz-Ríos; R. Viedma; S. Gago; S. Ortega-Madueño; L. Alcazar-Fuoli; M. J. Buitrago (Journal of Fungi, 2025)
Diagnosis of histoplasmosis is challenging. A rapid, sensitive, and specific method is essential. Serum is a non-invasive and easy sample to obtain in any hospital. The diagnostic accuracy of different techniques that use serum has been evaluated. Forty-one serum samples from patients with proven or probable histoplasmosis were analyzed. Different diagnostic techniques based on the detection of antibodies (ID Fungal Antibody System), antigens (Histoplasma GM EIA and PlateliaTM Aspergillus Ag), and DNA (“in-house” real-time PCR (RT-PCR) were tested and compared. Additionally, the quantification of cytokines and biomarkers related to histoplasmosis was performed. Global results from 27 samples in which all the tests were performed showed that the sensitivity of the Histoplasma GM EIA kit was 87.5% in patients with disseminated infection and HIV as an underlying disease; in immunocompetent (IC) patients, it was 54.5%. The detection of Histoplasma spp. with the ID Fungal Antibody System was positive in 90.9% of IC and in 62.5% of HIV patients. The Platelia-Asp kit had a low performance in both groups of patients (37.5% in HIV and 9% in non-HIV), and, finally, RT-PCR was better in immunosuppressed patients (44% in HIV vs. 27% in non-HIV). The combination of diagnostic techniques increased the detection of Histoplasma infection in inmunosupressed patients. Overall, patient groups infected with H. capsulatum (Hc) showed higher IL-8, IL-6, IL-1β, TNF-α, and IL-18 median values compared to non-Hc-infected controls. The effectiveness of diagnostic techniques on serum samples is highly influenced by the patient’s clinical presentation and underlying condition. Consequently, a thorough assessment of the patient’s clinical presentation and disease phenotype is crucial in selecting the most suitable diagnostic method.